Ecosystem-based management of riparian forest resources: a five-year participatory forest management plan for Volta River in Nandom Municipality, Ghana - Kenneth Peprah; Raymond Aabeyir; Paul Kwame Nkegbe (Journal of Degraded and Mining Lands Management, 2022)
The combination of water and land ecosystems as found in riparian areas offers valuable ecosystem resources, in dryland areas. The aim of this paper was to draw a management plan for the utilisation, and protection of the riparian forests or woodlands along the Black Volta River in Nandom Municipality. An exploratory research design was used together with quantitative and qualitative approaches. A survey of 75 respondents from 10 communities, 10 key informant interviews, and five focus group discussions in five communities were used to collect primary data. Satellite images for 2001 and 2014 were sourced from USGS site. The results revealed that riparian forest loss was 6.4% over 13 years. There was an increase in bare area by 10.6% over the same period. The study identified 49 plant resources, 14 wildlife resources, and 25 halieutic resources. A five-year management plan was developed with community participation; the implementation of which would engender sustainability of the riparian ecosystem.